Improving energy efficiency in massive MIMO system with non ideal hardware / Abd Aziz Bakeri - Bakeri, Abd Aziz (2017)
Massive Multiple Input Multiple Output also known as Massive MIMO is promising next generation for wireless network technology, with large number of antenna at base station mean large scale radio frequency chains. It will be the biggest challenge to wireless communication system when energy consumption meets the needs of growing traffic. High cost for build Massive MIMO with Ideal hardware compare to Massive MIMO with non-ideal hardware. This study focus on comparison energy efficiency between ideal hardware and non-ideal hardware in Massive MIMO system. In this paper, energy efficiency has been analyses from N antenna at base station and single antenna user transceiver. Result shows massive MIMO non ideal hardware can achieve energy efficiency.